The Case for Compulsory DNA Testing at Birth to Confirm Paternity: Ethical, Legal, and Social Considerations - Willie, Michael Mncedisi (UI Scholars Hub, 2025)
Compulsory paternity testing at birth has sparked significant legal, ethical, and social debate due to its potential impact on family dynamics, child well-being, and parental responsibility. This review explores the ethical, legal, and societal implications of such testing, using Bioecological Systems Theory and Rawls' Theory of Justice to frame the discussion. This review evaluates the benefits and challenges of mandatory DNA testing at birth, particularly in reducing paternity fraud, ensuring fairness in child support allocation, and enhancing socio-economic outcomes, especially in low-income households. This qualitative review draws on multidisciplinary literature from family law, genetic counseling, social policy, and fathers' rights advocacy. Sources were identified through PubMed, Scopus, and Google Scholar, alongside grey literature such as policy briefs and advocacy reports (e.g., Fathers 4 Justice SA). Search terms included